2014
DOI: 10.1007/s12020-014-0440-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and anatomic characteristics of benign and malignant adrenal masses on positron emission tomography/computed tomography: a review of literature

Abstract: PET/CT with (18)F-fluorodeoxyglucose (FDG) or using different radiocompounds has proven accuracy for detection of adrenal metastases in patients undergoing cancer staging. It can assist the diagnostic work-up in oncology patients by identifying distant metastases to the adrenal(s) and defining oligometastatic disease that may benefit from targeted intervention. In patients with incidentally discovered adrenal nodules, so-called adrenal "incidentaloma" FDG PET/CT is emerging as a useful test to distinguish beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 214 publications
(256 reference statements)
1
20
1
2
Order By: Relevance
“…From our analysis, patients with primary lung malignancy had almost 11 times greater chance of harboring an adrenal metastasis than those with non-lung primary malignancy. This is consistent with the finding that lung primary malignancy is the most common malignancy metastasizing to the adrenals [1][2][3][10][11] . Using an optimal cut-off of 2.65, those with SUVmax >2.65 had a 31.6 times greater chance of adrenal metastasis than those with SUVmax ≤2.65.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…From our analysis, patients with primary lung malignancy had almost 11 times greater chance of harboring an adrenal metastasis than those with non-lung primary malignancy. This is consistent with the finding that lung primary malignancy is the most common malignancy metastasizing to the adrenals [1][2][3][10][11] . Using an optimal cut-off of 2.65, those with SUVmax >2.65 had a 31.6 times greater chance of adrenal metastasis than those with SUVmax ≤2.65.…”
Section: Discussionsupporting
confidence: 92%
“…Our data found that the history of primary lung malignancy (odds ratio=11.91, 95%CI 1.30 -111. 1) and SUVmax (odds ratio=1.66, 95%CI=1.09 -2.52) were significant risk factors for adrenal metastasis. From our analysis, patients with primary lung malignancy had almost 11 times greater chance of harboring an adrenal metastasis than those with non-lung primary malignancy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Lin et al observed that FDG-PET/CT was not able to differentiate between benign and malignant lesions in patients with HCC [16]. However, FDG-PET/CT emerged as an adjunctive diagnostic tool in the evaluation of incidental adrenal lesions in order to distinguish benign from malignant adrenal nodules and for the overall preoperative staging [17,18]. Therefore, FDG-PET/CT is currently used more frequently, e.g., in patients with bronchial tumors.…”
Section: Main Findingsmentioning
confidence: 99%